HYBRID AUDIT: KEAHLIAN DAN INTEGRITAS AUDITOR TERHADAP KINERJA LAPORAN HASIL AUDIT DI ERA DIGITALISASI - Mulyandini, Vita Citra; Anggionaldi, Muhammad (Worksheet : Jurnal Akuntansi, 2025)
Digital transformation has transformed the audit landscape, requiring auditors to master not only conventional technical aspects but also adaptive capabilities in technology and data analytics. This study aims to examine the role of auditor expertise and integrity in improving audit report performance in the digital era through a literature review approach. This study analyzes various scientific publications and articles related to the topic of hybrid auditing, which combines technological and accounting expertise with professional integrity as the main foundation. The review results indicate that information technology competence, understanding of digital systems, and the ability to process big data are crucial factors in supporting the reliability of audit reports. Integrity remains a fundamental element in maintaining objectivity, independence, and ethics in audit implementation. This study recommends the development of continuous training for auditors in the field of technology and the instilling of integrity values as a strategy towards effective, efficient, and reliable audits in the digital era.